Perspectives on Practice: Film preservation policy in Ireland—the politics of omission - OConnell, Kasandra (Irish Journal of Arts Management and Cultural Policy, 2024)
Ireland is one of the few western nations without a state sanctioned archive or policy for moving image preservation. This lack of a formally authorised national moving image collection or policy to protect it is surprising given Ireland’s membership of the European Union (EU), a supranational organisation that has stressed the importance of film heritage to society for decades and encourages member states to proactively preserve and disseminate their national film collections. Despite this, Ireland has neglected to implement EU film heritage recommendations and, whilst moving image preservation has been sporadically discussed at government level, it has never been deemed worthy of a specific policy, legislation or resultant safeguards. The absence of policy in this area has shaped official thinking and attitudes towards Irish moving image heritage, with support for preservation sporadic and ad hoc in nature. Policy and funding have concentrated on the production and distribution of new moving image works rather than the preservation and dissemination of heritage material. This paper utilises the author’s experience as Head of the Irish Film Institute’s (IFI) Irish Film Archive (IFI Archive) to explore this imbalance in Ireland’s film related policy and the practical consequences of this omission. It looks at recent cultural policy and strategy documents for evidence of film heritage provision and frames the findings within recent academic discourse examining the neoliberal turn in Irish cultural policy. Finally, it suggests possible solutions to safeguard and heritage moving image collections.